Low-velocity impact response of fibre–metal laminates – experimental and finite element analysis - Zhu, Shengqing (2013)
In this contribution, the impact dynamic response and failure modes of fibre–metal laminated panels subjected to low velocity impact were investigated and presented. The fibre–metal laminate in this paper comprised of a layer of glass fibre-reinforced plastics sandwiched between two layers of aluminium alloy. Two different types of glass fibre-reinforced plastics were used for the fabrication: unidirectional and woven. A fairly extensive experimental investigation was conducted in conjunction with a detailed finite element analysis. The experiments were conducted using a standard drop-weight test machine and the finite element analysis was carried out using a commercially available finite element software. The results of maximum contact force, contact duration and corresponding failure modes are presented, compared and discussed in this technical paper.